Analisis Efektivitas Penginputan Surat Pertanggungjawaban (SPJ) pada Aplikasi Sistem Informasi Pengelolaan Keuangan Daerah (SIPKD) dan Sistem Informasi Pemerintahan Daerah (SIPD) dalam Mendukung Akuntabilitas Keuangan Daerah Periode Tahun 2024 – 2025 (S - Syarafina Dewi, Nur; Budiana Kurniawati, Susilaningtyas; Abdullah, Syahriar (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the effectiveness of inputting Accountability Reports (SPJ) through two main systems: the Regional Financial Management Information System (SIPKD) and the Regional Government Information System (SIPD), in supporting financial accountability at the Selogiri Sub-District Office, Wonogiri Regency. A qualitative descriptive approach was used, with data collected through observation, in-depth interviews, and documentation. The results show that SIPKD is more operationally effective due to its flexibility, offline accessibility, and robust data validation system. On the other hand, SIPD offers advantages in terms of national data integration but still faces technical challenges such as dependence on internet connectivity and heavy server loads. Barriers to the effectiveness of SPJ input include limited human resources, lack of technical training, and suboptimal integration between SIPKD and SIPD. This study concludes that the success of regional financial management is determined not only by the sophistication of the system but also by the readiness of human resources and the adequacy of supporting infrastructure.